Methodological approaches to assess climate vulnerability and cumulative impacts on coastal landscapes - Olivares-Aguilar, Isabel C.; Sánchez-Dávila, Gabriel; Wildermann, Natalie Elizabeth; Clark, Dana; Floerl, Lisa; Villamizar, Estrella; Matteucci, Silvia D.; Muñoz Sevilla, Norma Patricia; Nagy, Gustavo J. (Frontiers in Climate, 2022)
Natural and anthropogenic hazards and climate risks threaten marine and coastal ecosystems worldwide, with severe consequences for these socio-ecological systems. Therefore, assessing climate vulnerability and cumulative environmental impacts of multiple hazards is considered critical in coastal planning and management. We review the approaches used for its evaluation to know the state of the art of the subject. First, we assess the climate vulnerability of five coastal regions of Venezuela using indicators related to the IPCC Reasons for Concern and Climate Risks, RFC-1, RFC2, RFC4 and RFC5. Also, we assess the cumulative environmental impact of 14 climate stressors in 16 marine and terrestrial ecosystems, modifying the method of Halpern (2008) and incorporating climatic variables. We found no standardization of the methodologies used in evaluating Coastal Climate Vulnerability or Cumulative Environmental Impacts in coastal landscapes, nor frameworks that operationally link them with socio-ecological systems. However, we found five regions of Venezuela at risk from at least three of the analyzed RFCs, including; loss of unique ecosystems and risks associated with extreme events. The impact model showed areas ranging from a moderate to a high level of accumulated impact of anthropic and natural pressures that cover 9.93% (102,471Ha) located on the western coast of the Paraguaná Peninsula, the central coast, the Golfete de Coro and the area of flooding of the Isthmus of the Médanos in which urban areas, growth zones, industrial oil settlements, port areas and aquaculture areas with fishing activity are found. In addition, areas with moderate to low cumulative impact that covers about 43.74% (455,345Ha) are located in the Paraguaná Peninsula and flood-prone areas of the Mitare Delta with “thorny scrub” and “coastal grassland” type vegetation. We consider that it is imperative to implement adaptation measures against climate risks because of the lack of such kind of evaluations in the ordinance in the region, especially in countries like Venezuela that are particularly vulnerable to climate change due to harsh weather conditions and poor economic conditions. Finally, we present the scope and limitations of implementing these assessments and highlight the importance of incorporating them into the regional climate change adaptation strategies.